PENGARUH PUTARAN PULLY (RPM) DAN TEKANAN TERHADAP PRODUKTIVITAS MESIN PEMECAH BIJI KEMIRI - Anggara , Mietra; Jibril, Aburijal (Jurnal TAMBORA, 2021)
Candlenut is a spice that is used as an ingredient in the manufacturing process of the food and cosmetic industry, the obstacles faced in breaking the candlenut shell are that the time and energy required is still too large so that the splitting of the candlenut shell is less efficient and there are still many farmers who still use traditional candlenut crackers. with a driving force in the form of human power. In addition, the results of the quality of the candlenut cracking are not good because there are still many broken hazelnut seeds after the process of breaking the candlenut shell. These constraints add to the time, cost and effort in the process of breaking candlenut manually. From some of the constraints that have been described, there is an idea to conduct research to find out how the rotation of the candlenut crusher influences the pressure according to the needs and optimizes the rotation variation of the candlenut crusher to produce whole candlenuts. The research method used is rotational variation (10 RPM, 20 RPM, and 27 RPM) to pressure 24.928 /????2, 21.952 /????2 and 19.286 /????2 with three treatments and each treatment combination was repeated three times. The parameters of this research are the percentage of whole, split, crushed and unbroken candlenut. The results of this study indicate that variations in rotation and pressure affect the percentage yield of candlenut seeds. The average value of the right rotation to break candlenut seeds with a beating pully A is 20 rpm with a pressure of 24.928 N/m2 to get an average of 60% intact, 20% halved, 0% crushed and 20% unbroken. At the right rotation of the pulley B, which is at 20 Rpm with a pressure of 21.952 N/m2, the average value of breaking is 60%, intact is 60%, split is 30%, destroyed is 0% and does not break is 10%. Meanwhile, at a pressure of 19.286 N/m2 for a rotation of 20 Rpm, the average value of broken, 50% intact, 0% halved, 20% crushed and 30% unbroken.